Factors related to quilombola attendance to child follow-up appointments - Elenilda Farias de Oliveira; Climene Laura de Camargo; Nadirlene Pereira Gomes; Telmara Menezes Couto; Luana Moura Campos; Patricia Santos de Oliveira
ABSTRACT Objective: To understand factors interfering with the attendance of quilombola children to growth and development follow-up appointments. Method: It is a qualitative research based on Symbolic interactionism, during which 14 mothers of children bellow 1 year-old were interviewed, who attended to the Family Health Unit at Ilha de Maré, Bahia, Brazil. Results: Appointment attendance is affected by factors intrinsic to mothers (meaning of child health follow-up; association between appointments and children falling ill; personal issues) and extrinsic factors, related to the service (availability, long waiting time for appointments and its quality). Final considerations: An administration prioritizing the service's organization is required, which can prioritize attendances and the reduction of waiting time, specially given the personal issues that compromise going to the unit.